Ruthenium(II) bipyridine complexes incorporating (NN′S) azoimine ancillary ligands. Synthesis, spectroscopy, solid state structure and DFT calculations. (17th February 2017) - Al-Noaimi, Mousa; Awwadi, Firas F.; Atallah, Bara; Taher, Deeb; Hammoudeh, Ayman; Lang, Heinrich; Rüffer, Tobias
Graphical abstract: Four ruthenium complexes bearing new (NN′S) azoimine-thiomethyl ligands L of the general type trans -[Ru II (bpy)(L)(Cl)2 ] ( C1 – C4 ) (L = YC6 H4 NNC(COCH3 )NC6 H4 (2-SMe), Y = H (L1), C1 ; CH3 (L2), C2 ; Br (L3), C3 ; NO2 (L4), C4 ) have been synthesized, by the reaction of ruthenium trichloride trihydrate with the corresponding L ligands and bipyridine in refluxing ethanol. The molecular structure of trans -[Ru(bpy)(L3)(Cl)2 ] (C3 ) in the solid state is reported. The azoimine-thiomethyl ligands (L) bind as NN′ bidentate ligands with no direct Ru–S interactions. Furthermore, the complexes have been characterized by spectroscopic (IR, UV/Vis and NMR 1 H) and cyclic voltammetry data. The electrochemical parameters (EL (L)) of the azoimine ligands ( L1 – L4 ) are reported. The electronic excitations of a representative complex (C3 ) are interpreted by DFT and TDDFT calculations. Abstract: Four ruthenium complexes of N'NS donor thiomethyl-azoimine ligands (L) of the general type trans -[Ru II (bipy)(L)(Cl)2 ]( C1 – C4 ) (L = XC6 H4 NNC(COMe)NC6 H4 (2-SMe), X = H (L1), C1 ; CH3 (L2), C2 ; Br (L3), C3 ; NO2 (L4), C4 ) have been synthesized by the reaction of ruthenium trichloride trihydrate with the corresponding L ligands and bipyridine (bipy) in refluxing ethanol. The molecular structure of trans -[Ru(bpy)(L3)(Cl)2 ](C3 ) in the solid state is reported. The thiomethyl-azoimine ligands (L) bind as NN′ bidentate ligands with no direct Ru–S interaction. Furthermore, the complexes have been characterized by spectroscopic data (IR, UV/Vis and 1 H NMR) and cyclic voltammetry. The electrochemical parameters ( EL ( L )) of the azoimine ligands (L1–L4) are reported. The electronic excitations of a representative complex (C3 ) are interpreted by DFT and TDDFT calculations.